Politik Lokal: Tinjauan Systematic Literature Review - Wahyu Trisno Aji (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to find out issues regarding local politics in Indonesia. The method in this research itself uses the systematic literature review (SLR) research method which uses 296 scientific articles sourced from Google Scholar using the Publish of Perish (POP) application. The review of this article uses the VosViewer application. The results of this research itself are based on a search for evidence from the POP database literature, revealing how the development of the local political system in Indonesia can be seen as very interesting to study from reference sources or references to previous studies. It is hoped that the results of this research will be a contribution to thinking about writing further articles on the same theme in politics in Indonesia. This research is not free from limitations because this research only uses Google Scholar research sources with the help of the POP application so this research is still far from being perfect as research on local political issues. Therefore, it is hoped that future research will need to use more authentic articles and it is recommended to use articles sourced from internationally reputable articles such as Scopus, Web of Science Dimensions Scholars, PubMed, and so on.